Artefactual "in‐vitro coagulopathy" in a patient with non‐Hodgkin lymphoma and lower gastrointestinal bleeding. Issue 5 (17th March 2014) - O'Day, Roderick; Ahlenstiel, Golo; Chittaranjan Shetty, Anita; Favaloro, Emmanuel J; Williams, Stephen J; Koutts, Jerry
Clinical record: An 80‐year‐old man presented in August 2012 with lower gastrointestinal bleeding 3 days after a routine colonoscopy and polypectomy as a day procedure. Five sessile polyps had been excised from the right colon (one from the caecum, one from the hepatic flexure and three from the transverse colon); the largest polyp measured 8 mm. Additionally, a 20 mm sessile polyp was excised from the rectum by means of chromogel elevation and endoscopic mucosal resection. 1 A resultant defect in the muscularis propria was closed with five endoclips. The patient was discharged in the evening, well after the procedure. Subsequent histopathological examination showed that the polyps were tubular or tubulovillous adenomas without dysplasia. Three days after initial polypectomy the patient was woken from sleep by abdominal discomfort and an episode of passing about 500 mL of fresh blood from the rectum. On presenting to the emergency department, he continued to bleed, although at a slower rate. He was asymptomatic and haemodynamically stable. His haemoglobin level was 115 g/L (reference interval [RI], 130–180 g/L) on presentation, and dropped to 98 g/L after a second large bleed 8 hours later. His blood urea nitrogen level on admission was elevated (12.6 mmol/L; RI, 3.0–8.0 mmol/L), consistent with a gastrointestinal bleed. The patient had multiple medical comorbid conditions, including non‐Hodgkin lymphoma (NHL). He had relapsed with NHL a month earlier with a rise in his IgM paraprotein levels to 5.0 g/L (RI, 0.0 g/L) after 8 years in remission. He also had hypertension, ischaemic heart disease, Paget disease and prostate cancer. Previous surgery included repair of type B aortic dissection and a splenectomy. His medications on admission included aspirin, simvastatin, amlodipine, metoprolol and frusemide. Initial results of blood tests (Table) showed an apparent coagulopathy, with a prolonged prothrombin time (PT) and activated partial thromboplastin time (APTT), an international normalised ratio (INR) of 2.0, but a normal thrombin time. The haematology team was consulted to assess and, if necessary, haemostatically correct the apparent coagulopathy before endoscopic assessment. 2, 3 The differential diagnoses of concurrently prolonged APTT and PT are concomitant warfarin and heparin therapy, supratherapeutic warfarinisation or heparinisation, inherited clotting factor deficiencies, acquired clotting factor deficiencies (secondary to disseminated intravascular coagulation, liver disease or vitamin K deficiency) and acquired inhibitors of clotting factors. 4 The patient was not receiving anticoagulation therapy. He had no previous history of bleeding or liver disease, and his fibrinogen levels were high (5.6 g/L; RI, 2.0–4.3 g/L), arguing against an acquired or hereditary clotting factor deficiency. Most importantly, mixing studies (which combine patient plasma with donor plasma that contains a normal concentration of clotting factors) did not correct the apparent coagulopathy. This is in keeping with the presence of either a clotting factor inhibitor or antiphospholipid antibodies. 4 Further investigations showed moderately positive lupus anticoagulant levels and no specific factor VIII or IX inhibitor. Lymphoproliferative disorders are well known to cause abnormalities of coagulation studies and, in particular, can cause lupus anticoagulant activity. 5 It was concluded that the apparent coagulopathy was an in‐vitro phenomenon caused by an interaction between lupus anticoagulant and the reagents used in the coagulation studies. In the absence of any clinical features of antiphospholipid syndrome, it was considered that there was no need for active treatment for the lupus anticoagulant results, which would have consisted of anticoagulant therapy. 6 After prompt resolution of the possible coagulopathy issue by laboratory staff and haematologists (ie, establishing that there was indeed no in‐vivo coagulopathy), the patient underwent urgent flexible sigmoidoscopy for ongoing rectal bleeding that evening, 17 hours after presentation. He was found to have active bleeding from the complicated rectal polypectomy site. Haemostasis was achieved with thermocoagulation and clipping. He recovered well and was discharged home 48 hours later having experienced no further bleeding and maintaining stable haemoglobin levels. Results of the patient's coagulation studies on admission: Study Value Reference interval Prothrombin time (PT) 25 seconds 11–18 seconds Activated partial thromboplastin time (APTT) 75 seconds 25–36 seconds International normalised ratio 2.0 na Mixing study No correction of prolonged APTT and PT Thrombin time 16 seconds 10–17 seconds : na = not applicable.